PENGARUH MARKET POWER DAN CAPITAL ADEQUACY RATIO (CAR) TERHADAP RISIKO LIKUIDITAS PERBANKAN DENGAN BANK LOAN DAN FIRM SIZE SEBAGAI VARIABEL KONTROL (Studi Kasus Pada Bank yang Terdaftar di BEI periode 2016-2020) - Ayu Mutiara Pramono, Nimas Sekar; Prasetiono, Prasetiono (Diponegoro Journal of Management, 2024)
ABSTRACT This study aims to determine the impact of market power and capital adequacy ratio on the liquidity risk of banking companies, with bank loan and firm size as control variables. Liquidity risk is measured by LDR, which compares total bank loans to total deposits. The samples in this study consist of banking companies listed on the Indonesia Stock Exchange (IDX) during the period from 2016 to 2020. A total of 40 companies were selected through purposive sampling. The analysis method employed in this study is multiple linear regression using the Ordinary Least Square approach. The results of this study indicate that the capital adequacy ratio has a positive and significant impact on liquidity risk. Market power on the other hand, have a negative and significant impact on liquidity risk